Challenges and opportunities of delivering IP-based residential television services. - Hastings, K. (IEEE Communications magazine)
This article describes the main challenges of implementing an end-to-end architecture for delivery of high-quality, IP-based residential TV services to residential customers. The IP-based approach can be implemented with an IP multicast overlay network with traditional routers or use IP-multicast-aware ATM switching systems. Both approaches use IP multicast to transport MPEG-2 broadcast video and can work on any access architecture, especially on copper-based architectures (xDSL) such as ASDL and VDSL. The main challenges met while implementing the IP-based architecture are competitive positioning relative to traditional CATV architectures, overall architecture, head-end architecture and quality issues, traffic engineering for stringent QoS requirements, IP multicast requirements, and business case considerations. The IP-based approach described leverages Internet technology advancements and capitalizes on the impacts of Internet on interactive entertainment. Video channel manipulation at the head-end is dependent on access bandwidth and affects video quality. Video traffic management to meet stringent QoS requirements is challenging at the IP layer. High-capacity, responsive IP multicasting is essential to achieving high service quality. Cost-effective IP multicasting is a critical component of the business case.